Systemic pharmacological interventions for Ménière’s disease - Webster, K; Harrington-Benton, NA; Judd, O; Kaski, D; Maarsingh, OR; MacKeith, S; Ray, J; Van Vugt, VA; Burton, MJ (Cochrane Collaboration, 2023)
Background Ménière's disease is a condition that causes recurrent episodes of vertigo, associated with hearing loss and tinnitus. A number of pharmacological interventions have been used in the management of this condition, including betahistine, diuretics, antiviral medications and corticosteroids. The underlying cause of Ménière's disease is unknown, as is the way in which these treatments may work. The efficacy of these different interventions at preventing vertigo attacks, and their associated symptoms, is currently unclear. Objectives To evaluate the benefits and harms of systemic pharmacological interventions versus placebo or no treatment in people with Ménière's disease. Search methods The Cochrane ENT Information Specialist searched the Cochrane ENT Register; Central Register of Controlled Trials (CENTRAL); Ovid MEDLINE; Ovid Embase; Web of Science; ClinicalTrials.gov; ICTRP and additional sources for published and unpublished trials. The date of the search was 14 September 2022. Selection criteria We included randomised controlled trials (RCTs) and quasi‐RCTs in adults with definite or probable Ménière's disease comparing betahistine, diuretics, antihistamines, antivirals or systemic corticosteroids with either placebo or no treatment. We excluded studies with follow‐up of less than three months, or with a cross‐over design (unless data from the first phase of the study could be identified). Data collection and analysis We used standard Cochrane methods. Our primary outcomes were: 1) improvement in vertigo (assessed as a dichotomous outcome ‐ improved or not improved), 2) change in vertigo (assessed as a continuous outcome, with a score on a numerical scale) and 3) serious adverse events. Our secondary outcomes were: 4) disease‐specific health‐related quality of life, 5) change in hearing, 6) change in tinnitus and 7) other adverse effects. We considered outcomes reported at three time points: 3 to < 6 months, 6 to ≤ 12 months and > 12 months. We used GRADE to assess the certainty of evidence for each outcome. Main results We included 10 studies with a total of 848 participants. The studies evaluated the following interventions: betahistine, diuretics, antivirals and corticosteroids. We did not identify any evidence on antihistamines. Betahistine Seven RCTs (548 participants) addressed this comparison. However, we were unable to conduct any meta‐analyses for our primary outcomes as not all outcomes were considered by every study, and studies that did report the same outcome used different time points for follow‐up, or assessed the outcome using different methods. Therefore, we were unable to draw meaningful conclusions from the numerical results. Some data were available for each of our primary outcomes, but the evidence was low‐ or very low‐certainty throughout. One study reported on the outcome 'improvement in vertigo' at 6 to ≤ 12 months, and another study reported this outcome at > 12 months. Four studies reported on the change in vertigo, but again all used different methods of assessment (vertigo frequency, or a global score of vertigo severity) or different time points. A single study reported on serious adverse events. Diuretics Two RCTs addressed this comparison. One considered the use of isosorbide (220 participants), and the other used a combination of amiloride hydrochloride and hydrochlorothiazide (80 participants). Again, we were unable to conduct any meta‐analyses for our primary outcomes, as only one study reported on the outcome 'improvement in vertigo' (at 6 to ≤ 12 months), one study reported on change in vertigo (at 3 to < 6 months) and neither study assessed serious adverse events. Therefore, we were unable to draw meaningful conclusions from the numerical results. The evidence was all very low‐certainty. Other pharmacological interventions We also identified one study that assessed antivirals (24 participants), and one study that assessed corticosteroids (16 participants). The evidence for these interventions was all very low‐certainty. Again, serious adverse events were not considered by either study. Authors' conclusions The evidence for systemic pharmacological interventions for Ménière's disease is very uncertain. There are few RCTs that compare these interventions to placebo or no treatment, and the evidence that is currently available from these studies is of low or very low certainty. This means that we have very low confidence that the effects reported are accurate estimates of the true effect of these interventions. Consensus on the appropriate outcomes to measure in studies of Ménière's disease is needed (i.e. a core outcome set) in order to guide future studies in this area and enable meta‐analyses of the results. This must include appropriate consideration of the potential harms of treatment, as well as the benefits.